Answer:
y = -3x - 1
Step-by-step explanation:
Let he equation of the line is,
y = mx + b
Here, m = slope of the line
b = y-intercept
Slope 'm' of the line passing through two points
and
is,
m = ![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Slope of the line passing through (-2, 5) and (2, -7) will be,
m = ![\frac{-7-5}{2+2}](https://tex.z-dn.net/?f=%5Cfrac%7B-7-5%7D%7B2%2B2%7D)
m = -3
Equation of the line will be,
y = -3x + b
Since, this line passes through (-2, 5),
5 = -3(-2) + b
5 = 6 + b
b = 5 - 6
b = -1
Therefore, equation of the line will be,
y = -3x - 1